The Process in the Quantum Ontology: The non-existence of being in the present point - Sáez Acuña, José Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This paper on the basis of mathematics revisits traditional ontological concepts. It proposes a model that relates differential calculus and linguistic expressions, specifically it discusses Romance Ser and Estar, and argues that the first is derived from the latter denoting a causal relationship. This paper departs from the notion of «present» from physics to approach the non-existence of to be discussing grammar and, specifically, the present tense of TO BE. We conclude that it is not possible to claim that somos, but merely that estamos. Finally, this paper discusses some implications of this model to social life.
Keywords: to be; causality; metaphysics; mathematics; physics.